VSSO Kalman-usage of Barhumi's pilot pattern for channel estimation in MIMO-OFDM systems - Karthik, M. (2013)
Vector state-scalar observation (VSSO) and vector state-vector observation (VSVO) are two types of Kalman channel estimators used in orthogonal frequency division multiplexing (OFDM) systems. VSSO Kalman channel estimators result in over 90% complexity savings, compared to VSVO Kalman channel estimators, without any loss of performance. Thus far, for frequency-selective channels, VSSO Kalman channel estimators have been proposed only for OFDM systems and not for MIMO-OFDM systems. VSVO Kalman channel estimators have been proposed for MIMO-OFDM systems over frequency- selective channels. Proposed is a VSSO Kalman channel estimator for MIMO-OFDM systems using Barhumi’s pilot pattern. It will be seen that the proposed VSSO Kalman channel estimator has much better performance than the method of Barhumi’s least-squares method (literature method) and this is achieved with only a moderate increase (two times) in complexity. Similarly, the proposed VSSO Kalman channel estimator has the same performance as the VSVO Kalman channel estimator method (literature method) and this is achieved at about (1/60)th of the complexity associated with the VSVO method.